Community forestry: Small groups, large forests - Henneke, Ben (Technical Centre for Agricultural and Rural Cooperation, 2011)
Farmers working with the International Small Group and Tree Planting Program have been using handheld computers and portable GPS receivers since 1999 to collect data for carbon credit trading. In that time, the project has planted more than twenty million trees in six countries.